Study of Thermal Decomposition Kinetics of Palm Oleic Acid-Based Alkyds and Effect of Oil Length on Thermal Stability - Ataei, Shahla; Yahya, Rosiyah; Gan, Seng Neon; Hassan, Aziz (Springer Verlag, 2012)
Thermal decomposition kinetics of three palm oleic acid-based alkyds with different oil lengths and having different molecular weights were studied using TGA measurements under non-isothermal conditions. Activation energies were obtained from Kissinger and Ozawa, Flynn and Wall (OFW) methods and subsequently the pre-exponential factor, A, degradation rate constant, k, for all the alkyds were also determined. From kinetic analysis of the thermal decomposition using the OFW method, it was found that degradation of all the alkyds has taken place in more than two stages, corresponding to different mechanisms. As shown from Ozawa and Kissinger methods, the chemical composition of the alkyds influenced the thermal degradation; increasing the phthalicanhydride and glycerol, and decreasing the oleic acid increased the thermal stabilities of the alkyds.